The 24-Hours Food Recall System for Monitoring Diabetes Melitus Patients - Framita Rahman; Ika Nurlaili Isnaniyah; Mutiara Cyesa P Ngandoh; Wiwi Saputri; Puspa Akhlakul Karimah (Berkala Kedokteran, 2023)
Abstract:Diabetes Mellitus is one of the diseases that can cause complications for patients if neglected and is one of the causes of most death cases in Indonesia. This study aims to build a website-based system to help monitor nutrition for DM patients through 24 hours food recall (24HFR). The 24HFR system will integrate the roles of nurses and nutritionists in hospitals to understand patient eating behaviour and formulate nutrition education for patients. This system is built based on the SDLC stages, from the needs analysis stage to testing and implementing the program. The usability test results using SEQ show that health workers can easily use the website-based 24HFR system.